The presence of Plasmodium malariae and Plasmodium knowlesi in near malaria elimination setting in western Indonesia - Irbah Rea Alvieda, Nainggolan; Rycha Dwi, Syafutri; Monica Nadya, Sinambela; Clara, Devina; Handayani, .; Beby Syofiani, Hasibuan; Sriwipa, Chuangchaiya; Paul Cliff Simon, Divis; Zulkarnain Md, Idris; Ranti, Permatasari; Inke Nadia Diniyanti, Lubis (BioMed Centre Ltd, 2022)
Background Indonesia is progressing towards malaria elimination. To achieve this goal, intervention measures must be addressed to cover all Plasmodium species. Comprehensive control measures and surveillance programmes must be intensified. This study aims to determine the prevalence of microscopic and submicroscopic malaria in Langkat district, North Sumatera Province, Indonesia.